Visualizing Intrinsic 3D‐Strain Distribution in Gold Coated ZnO Microstructures by Bragg Coherent X‐Ray Diffraction Imaging and Transmission Electron Microscopy with Respect to Piezotronic Applications. (11th August 2021) - Jordt, Philipp; Wolff, Niklas; Hrkac, Stjepan B.; Shree, Sindu; Wang, Di; Harder, Ross J.; Kübel, Christian; Adelung, Rainer; Shpyrko, Oleg G.; Magnussen, Olaf M.; Kienle, Lorenz; Murphy, Bridget M.
Abstract: Novel devices ranging from bio magnetic field sensors to energy harvesting nano machines utilize the piezotronic effect. For optimal function, understanding the interaction of electrical and strain phenomena within the semiconductor crystal is necessary. Here, studies of a model piezotronic system are presented, consisting of a ZnO microrod coated by a thin layer of gold, which forms a Schottky contact with the piezoelectric ZnO material. Coherent X‐ray diffraction imaging (CXDI) and transmission electron microscopy (TEM) are used to visualize the structure and strain distribution, showing that the ZnO microrod exhibits strains of multiple origins in the bulk and at the interface. Strain values of −6 × 10 ‐4 have been measured by CXDI at the ZnO/Au interface. The origin is shown to be a combination of an interface strain, possibly caused by the Schottky contact formation, and distinct, localized electrical fields inside the crystal which are assigned to electron depletion and screening in a bent ZnO/Au piezotronic rod. These findings will contribute to sensor development and to a better understanding of piezotronic applications. Abstract : Zinc oxide microstructures coated with gold are investigated by complementary geometric phase analysis on transmission electron micrographs and coherent X‐ray diffraction imaging (CXDI) revealing strain distributions with compressive strain near the Au interface. CXDI furthermore visualizes a non‐symmetric strain inside a ZnO rod, attributed to electron depletion and potential screening occurring in bent piezotronic structures.